2020
DOI: 10.7150/thno.45674
|View full text |Cite
|
Sign up to set email alerts
|

CSRP2 suppresses colorectal cancer progression via p130Cas/Rac1 axis-meditated ERK, PAK, and HIPPO signaling pathways

Abstract: Metastasis is a major cause of death in patients with colorectal cancer (CRC). Cysteine-rich protein 2 (CSRP2) has been recently implicated in the progression and metastasis of a variety of cancers. However, the biological functions and underlying mechanisms of CSRP2 in the regulation of CRC progression are largely unknown. Methods: Immunohistochemistry, quantitative real-time polymerase chain reaction (qPCR) and Western blotting (WB) were used to detect the expression of CSRP2 in CRC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 55 publications
3
30
1
Order By: Relevance
“…Specifically, RAC1-mediated cell migration is initiated by BCAR1 37 . Furthermore, the BCAR1/Rac1 axis can suppress colorectal cancer and metastasis through the Hippo, ERK, and PAK signaling pathways 38 , indicating the signaling pathway is indispensable in cell signal transduction. In addition, RAC1 regulates EMT 39 , potentially via STAT343 40 , ERK2 41 and the nuclear translocation of ÎČ-catenin 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, RAC1-mediated cell migration is initiated by BCAR1 37 . Furthermore, the BCAR1/Rac1 axis can suppress colorectal cancer and metastasis through the Hippo, ERK, and PAK signaling pathways 38 , indicating the signaling pathway is indispensable in cell signal transduction. In addition, RAC1 regulates EMT 39 , potentially via STAT343 40 , ERK2 41 and the nuclear translocation of ÎČ-catenin 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The same research group could show in a study focusing on paxillin and protein tyrosine phosphatase receptor T (PTPRT) in CRC that phosphorylated Y88 in paxillin impacts the AKT pathway by controlling the interaction of the p85 regulatory PI3K subunit and p130Cas [26]. In a recent study, cysteine-rich protein 2 (CSRP2) was shown to inhibit p130Cas phosphorylation and subsequent Rac family small GTPase 1 (Rac 1) activation, thereby increasing the activity of the Hippo pathway and decreasing the p21-activated kinase (PAK)-cortactin and MAPK pathways [27]. This resulted in suppressed EMT in vitro and reduced tumorigenicity and metastasis of CRC in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified a potential association of BCAR1 expression with CRC [23]. Other studies showed the involvement of p130Cas in α1-integrin/c-Src-mediated invasion of CRC cells [24], in c-Src regulated PI3K/AKT-driven colon tumorigenesis [25,26], and cysteine-rich protein 2 (CSRP2) controlled suppression of CRC progression [27].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of in vivo experiments, it was shown that thiopurines treatments (TG) inhibited CAC in the AOM/DSS mouse model, via decreased ÎČ-catenin in a RAC1-dependent mechanism [ 144 ]. In the context of epithelial cell targeting, EMT and metastatic potential might be inhibited upon activation of RAC1; for instance, upon CSRP2 treatment (Hippo-ERK-PAK/LIMK/cortactin) [ 145 ], miR-142-3p transfection [ 146 ], upregulation of SSH3 (LIMK) [ 147 ] or PLS1 (ERK1/2) [ 148 ], downregulation of DMTN [ 149 ], or IRF1 suppression [ 150 ]. Recent work from An et al revealed the different behavior of RAC1 inhibition in combination with irradiation on cell cycle.…”
Section: Rac1 (Ras-related C3 Botulinum Toxin Substrate 1)mentioning
confidence: 99%